Incidence and Clinical Significance of Incidentally Detected Breast Lesions on Contrast-Enhanced Chest Computed Tomography in Thammasat University Hospital - Kwankua, Amolchaya; Sriwap, Somrudee; Lohitvisate, Wanrudee (Science & Technology Asia, 2021)
Increased use of the contrast-enhanced chest computed tomography (CT) has resulted in increased detection of unexpected breast lesions unrelated to the primary diagnostic questions. However, the breasts are not the primary focus of most chest CT scans, breast lesions are usually overlooked. The purpose of this study was to evaluate the incidence, clinical significance and CT features of incidentally detected breast lesions from routine contrastenhanced chest CT scans performed for reasons other than breast-related problems. A total of 1912 contrast-enhanced chest CT scans of female patients with no history of breast diseases performed between January 2013 and December 2014 were retrospectively reviewed. Incidental breast lesions were identified by two radiologists in consensus. The incidence, clinical significance, morphology and enhancement patterns of the incidentally detected breast lesions were evaluated. Forty-one (2.1%) patients had one or more incidentally detected breast lesions identified by chest CT scan. Of these, 12 (29.3%) patients had primary breast cancer, 19 (46.3%) patients had benign breast lesions and 10 (24.4%) patients had breast lesions with unknown pathology. The incidental detection rate of breast cancer was 0.6%. CT characteristic analysis showed a statistically significant difference between benign and malignant breast lesions in size, shape, margin and pattern of enhancement ( p<0.0001) . In conclusion, clinically unexpected breast cancer can be incidentally detected by contrastenhanced chest CT scans. Careful interpretation of the breasts in these scans may improve early diagnosis and treatment of breast cancer.